Assessing the AIR classification reliability for estimating pronation of the first metatarsal - Ning Sun; Xuewen Wang; Xiangyu Xu; Heng Li; Wenjing Li; Xiaofeng Gong; Hui Du; Yong Wu (BMC Musculoskeletal Disorders)
Abstract Background Hallux valgus (HV) is a multiplanar deformity and surgical treatment is often guided by two-dimensional radiographic parameters. This study assessed the reliability and accuracy of the AIR classification(The first metatarsal head’s lateral edge can be delineated as angular (type A), round (type R), or intermediate (type I) through visual inspection or circle measurements on weight-bearing radiographs.)commonly used in clinical settings to categorize the shape of the lateral edge of the first metatarsal head, against measurements from weight-bearing computed tomography (WBCT). Methods This retrospective study evaluated 18 patients, including 31 feet affected by HV. Two surgeons independently categorized the first metatarsal head’s lateral edge by both visual inspection and circle measurement. Additionally, two separate surgeons evaluated the α angle relative to the floor in WBCT scans. The reliability of the measurements was assessed using intraclass correlation coefficients (ICC) and weighted kappa statistics. Results While the first surgeon demonstrated perfect intra-observer reliability for both visual inspection and circular measurements (kappa values of 1.000 and 0.857, respectively), the second surgeon showed high and perfect reliability (kappa values of 0.759 and 1.000, respectively) for the same assessments. While the interobserver reliability for visual inspection was moderate (kappa values of 0.407 and 0.455, respectively), it was little to low for circular measurements (kappa values of 0.173 and 0.232, respectively). The interobserver reliability for the α angle assessment relative to the floor on WBCT scans was perfect (ICC = 0.968). Conclusion The AIR classification may not provide a reliable estimate of first metatarsal pronation, so clinicians should be cautious and recognize these limitations in their diagnostic applications. Between the two AIR classifications, the visual inspection measurement seems to be more reliable according to kappa value. If allowed, it may be better to additionally include a 3D assessment method such as WBCT, in the preoperative evaluation. Level of evidence IV, case series.